Automated Tire Pressure Control System for Multi-Purpose Wheeled Vehicles - Boikov, V. P.; Guskov, V. V.; Pavarekha, A. S. (БНТУ, 2021)
The cross-country capability of multi-purpose wheeled vehicles is one of the most important operational properties of these technical objects. In many ways, it is determined by their traction characteristics. There are a number of ways to improve traction and coupling properties of multipurpose wheeled vehicles, the main ones are the use of various kinds of traction control systems, blocking of interaxle and interwheel differentials, the use of ballast and several others. Recently, one of the ways to improve the traction properties and cross-country ability of vehicles on soils with weak load-bearing capacity is a regulation of air pressure in the tires of the driving wheels of multi-purpose wheeled vehicles. The paper describes the process of interaction of the wheel mover with the ground surface when the air pressure in the tire changes. The influence of air pressure on the traction properties of wheeled vehicles is established. The system of automatic control of air pressure in tires of mobile cars depending on road conditions is offered. The use of the proposed regulation principle will significantly increase the cross-country ability of multi-purpose wheeled vehicles in heavy traffic conditions, eliminating the subjective factor in the person of the vehicle operator.
Автоматизированная система регулирования давления воздуха в шинах многоцелевых колесных машин